Development of Formulas for Calculating L3 Skeletal Muscle Mass Index and Visceral Fat Area Based on Anthropometric Parameters - Ji, Wei; Liu, XiangLiang; Zhang, Yiqun; Zhao, Yixin; He, YuWei; Cui, JiuWei; Li, Wei (Frontiers in Nutrition, 2022)
Background: Anthropometric index is not accurate, but with great advance of accessibility. In order to proceed the universal nutrition screening, simple formulas of body composition should be explored. Methods: Clinical data of patients with malignant tumor of digestive system were collected. SliceOmatic 5.0 software (TOMOVISION, Canada) was used to analyze abdominal CT images and taken as references. Linear regression analysis was adopted to establish the formula of calculating SMI and VFA. And, relweights function was adopted to measure the contribution of each variable. Results: 344 patients were separated into the training set and 134 patients into the validation set. The selected formulas were SMI.pre = 0.540×weight (kg)-0.559* height (cm) –13.877×sex (male=1, female=2) +123.583, and VFA.pre = 5.146×weight (kg)-2.666×height (cm) +1.436×age (year) +134.096, of which the adjusted R2 were 0.597 and 0.581, respectively. The “weight” explained more than 80% of R2 in the prediction of VFA. And “sex” occupied approximately 40% of R2 in the prediction of SMI. Paired t-test showed no significant difference between the real measured indices and the predicting ones (P=0.123 for SMI and P=0.299 for VFA). Logistic regression analysis exhibited similar diagnostic efficacy of the real measured parameters and formulas. Conclusions: SMI and VFA formulas were developed through basic indices including weight, height, sex and age. According to the contribution of each variable, weight should always be focused on to preserve appropriate muscle and adipose tissue.